2015
DOI: 10.22279/navus.2015.v5n2.p51-59.248
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Ideas, Ideation and Idea Management

Abstract: Ideas are vital for organizations because they are the source for innovation and this in turn is endless source of competitive advantage. The correct definition of concepts not only allows the targeting of academic studies, but its future application in everyday life of organizations. The overall objective of this article is to clarify the terms related to generation of ideas, ideation and idea management. The method used was a literature review, and later, an analysis of the concepts used by the studies surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…There are several studies concerns on idea generation process and factors of new business idea selection which are for example, business performance, technological capabilities, marketing, financial, competitive and strategy. 6 –8 However, the research addressing the business ideas generation with Data Analytics (DA) for logistic business are still lacking. 9 Therefore, this paper introduces the investigation of suitable new business idea for couriers business considering DA opportunities in every stage of idea selection as Business Investigation, Idea Classification and Idea Selection.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies concerns on idea generation process and factors of new business idea selection which are for example, business performance, technological capabilities, marketing, financial, competitive and strategy. 6 –8 However, the research addressing the business ideas generation with Data Analytics (DA) for logistic business are still lacking. 9 Therefore, this paper introduces the investigation of suitable new business idea for couriers business considering DA opportunities in every stage of idea selection as Business Investigation, Idea Classification and Idea Selection.…”
Section: Introductionmentioning
confidence: 99%
“…At the dawn of the age of ideation and insight [49], the new tools of assessment based solely on standardized tests have evidently become insufficient. Rather than depending on standardized tests as the sole source of data to improve instruction, the DLFT framework envisions the use of the concept of big data in the service area of education.…”
Section: Discussionmentioning
confidence: 99%
“…Cleland & Ireland (2007) state that ideas that originate from community forums score greater acceptance and experience ease of implementation because they are owned by the beneficiaries. A study by Dorow et al (2015) on generation of ideas, ideation and idea Management concluded that it is important for an organization to practice inclusive ideas generation process because ideas are the source of creativity which becomes unlimited foundation for competitive advantage. To polish project ideas and ensure their significance, project developers perform arrays of activities to check the project's emphasis and alternatives (Flynn et al, 2011;Björk & Björk, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%